2016
DOI: 10.1007/s00540-016-2212-3
|View full text |Cite
|
Sign up to set email alerts
|

The plasma levels of brain-derived neurotrophic factor are positively associated with emergence agitation in the elderly after gastrointestinal surgery

Abstract: Our results suggest that plasma BDNF is associated with the occurrence of emergence agitation after gastrointestinal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…In addition, for proper prevention of EA, it would be helpful to identify a biomarker that could predict the occurrence of EA, based on preoperative blood sample examination. In elderly patients undergoing gastrointestinal surgery, the plasma level of brainderived neurotrophic factor (BDNF) collected at skin closure via blood sampling was significantly increased in patients with EA [73]. However, the study showed that the level of plasma BDNF collected before induction of anesthesia did not differ between patients who did and did not show EA; moreover, the study included only a limited number of well-selected patients.…”
Section: Prediction Of Emergence Agitationmentioning
confidence: 96%
“…In addition, for proper prevention of EA, it would be helpful to identify a biomarker that could predict the occurrence of EA, based on preoperative blood sample examination. In elderly patients undergoing gastrointestinal surgery, the plasma level of brainderived neurotrophic factor (BDNF) collected at skin closure via blood sampling was significantly increased in patients with EA [73]. However, the study showed that the level of plasma BDNF collected before induction of anesthesia did not differ between patients who did and did not show EA; moreover, the study included only a limited number of well-selected patients.…”
Section: Prediction Of Emergence Agitationmentioning
confidence: 96%
“…If the tracheal catheter is withdrawn at this time, the child will be more irritable, unable to cough, glossocoma, and have respiratory tract obstruction, SpO2 drop, hypercapnia, severe uncoordinated motion, or obvious disorientation. Intravenous anesthetics such as propofol, vecuronium, midazolam, or fentanyl may lead to postoperative psychiatric symptoms [ 21 ].…”
Section: Possible Mechanisms Of Eamentioning
confidence: 99%
“…Studies have confirmed that the use of sevoflurane and propofol for induction can help stabilize recovery after general anesthesia, proving that through enhanced GABA-mediated postsynaptic inhibition of the current, recovery from sevoflurane-induced anesthesia can be improved. There are experiments that prove that midazolam also enhances the inhibitory effect of the GABA receptor, and can also reduce the incidence of EA after anesthesia with sevoflurane inhalation [ 21 ]. Clinical findings have shown that the incidence of EA in children under five years old was significantly higher than that in adults after anesthesia with sevoflurane inhalation.…”
Section: Possible Mechanisms Of Eamentioning
confidence: 99%
“…Higher plasma BDNF levels were associated with emergence of agitation in elderly patients after gastrointestinal surgery [45]. In patients with spine surgery, an intraoperative decline in plasma BDNF was greater in patients who developed delirium [46].…”
Section: Studies Of the Relationship Between Circulating Bdnf Levels mentioning
confidence: 92%